Advantages and disadvantages of coronary drug-eluting stent: a 23-year journey of randomized clinical trials - Alfredo E. Rodriguez; Juan Mieres; Juan M. Rokos (Academia Medicine)
Introducing drug-eluting stents (DES2) significantly reduced target vessel revascularization (TVR), TVR-myocardial infarction (MI), and definitive stent thrombosis. Cardiac death in high-risk subgroups of lesions was also significantly reduced, and all of this is out of the discussion for the authors. However, that should be counterbalanced by the high incidence of spontaneous MI mainly due to early neo-atherosclerosis with DES. The finding of a high incidence of non-cardiac death observed in DES trials compared to coronary artery bypass grafting and optimal medical treatment is disturbing, and the reasons are unknown. Prompt action should be taken by the sponsors of the trials, scientific societies, and/or regulatory agencies to confirm or discard this intriguing observation. For now, it seems reasonable that DES2 should be indicated in all high-risk or high-complexity lesions; however, alternative strategies may be explored in all other scenarios until more information arrives. Time is running out.